(untitled) (Mongolian Journal of Chemistry, 2017)
A series of substituted triazin-pyridazine compounds were exhibited diverse types of biological activities and synthesized by different methods. These compounds were mainly tested for their anti-inflammatory, anticancer, antifungal and antibacterial activities. These substituted triazin-pyridazine compounds have mild to potent activities on compare with their appropriate reference standards.